Silks - Francis, Dick.; Francis, Felix (New York : G.P. Putnam's Sons, 2008)
Geoffrey Mason is well known (as "Perry" Mason) among the pro riders, including Steve Mitchell and Scot Barlow--arguably the two top pros. So when Scot Barlow is murdered--with Mitchell's pitchfork nonetheless--Geoff finds himself pulled into the case as a junior barrister.
Keywords: Steeplechasing -- England -- Fiction; Jockeys -- Crimes against -- Fiction; Mystery fiction; Legal stories